Stereoselective Silylcupration of Conjugated Alkynes in Water at Room Temperature1. (18th March 2014) - Linstadt, Roscoe T. H.; Peterson, Carl A.; Lippincott, Daniel J.; Jette, Carina I.; Lipshutz, Bruce H.
Abstract Micellar catalysis enables copper‐catalyzed silylcupration of a variety of electron‐deficient alkynes, thereby providing access to isomerically pure E‐ or Z‐β‐silyl‐substituted carbonyl derivatives. These reactions take place in minutes, afford high yields and stereoselectivity, and are especially tolerant of functional groups present in the substrates. The aqueous reaction medium has been successfully recycled several times, and a substrate/catalyst ratio of 10, 000:1 has been documented for this methodology.